Streptavidin aptamers: affinity tags for the study of RNAs and ribonucleoproteins. - Srisawat, C (2001)
RNA affinity tags would be very useful for the study of RNAs and ribonucleoproteins (RNPs) as a means for rapid detection, immobilization, and purification. To develop a new affinity tag, streptavidin-binding RNA ligands, termed "aptamers," were identified from a random RNA library using in vitro selection. Individual aptamers were classified into two groups based on common sequences, and representative members of the groups had sufficiently low dissociation constants to suggest they would be useful affinity tools. Binding of the aptamers to streptavidin was blocked by presaturation of the streptavidin with biotin, and biotin could be used to dissociate RNA/streptavidin complexes. To investigate the practicality of using the aptamer as an affinity tag, one of the higher affinity aptamers was inserted into RPR1 RNA, the large RNA subunit of RNase P. The aptamer-tagged RNase P could be specifically isolated using commercially available streptavidin-agarose and recovered in a catalytically active form when biotin was used as an eluting agent under mild conditions. The aptamer tag was also used to demonstrate that RNase P exists in a monomeric form, and is not tightly associated with RNase MRP, a closely related ribonucleoprotein enzyme. These results show that the streptavidin aptamers are potentially powerful tools for the study of RNAs or RNPs.